Description of females of Chilarboreus Ruta, 2011 (Coleoptera: Scirtidae: Scirtinae) - Ruta, Rafał; Yoshitomi, Hiroyuki (Zootaxa, 2018)
Chilarboreus is a small genus comprising three species occurring in Nothofagus forests of Chile. The female of a single species, Chilarboreus fossulatus, was described in the original description. In the present paper we provide descriptions of females of the remaining two species for the first time. Morphology of females supports the previous division of Chilarboreus into two subgenera. Pronotal excitators are described and illustrated for the first time in Scirtidae.